MeJA regulates the accumulation of baicalein and other 4’-hydroxyflavones during the hollowed root development in Scutellaria baicalensis - Geng, Dali; Jiang, Mei; Dong, Hongjing; Wang, Rongyu; Lu, Heng; Liu, Wei; Guo, Lanping; Huang, Luqi; Xiao, Wang (Frontiers in Plant Science, 2023)
The dried roots of Scutellaria baicalensis are important traditional Chinese medicine used to treat liver and lung inflammation. An anomalous structure, hollowed root, was discovered in perennial cultivated Scutellaria baicalensis. The presence of the hollow may change the contents of bioactive metabolites, such as baicalein, and other 4'-hydroxyflavones in Scutellaria baicalensis roots, but the relationship between the hollowed root and bioactive metabolite contents is poorly understood. In this study, we identified the anatomical structure of the hollowed root and detected differentially accumulating flavonoid metabolites and enzymes related to 4'-hydroxyflavone biosynthesis in 3-year-old roots with a hollow. We confirmed that methyl jasmonate (MeJA) induced the accumulation of 4'-hydroxyflavones and the expression of enzymes related to 4'-hydroxyflavone biosynthesis in hydroponically cultured Scutellaria baicalensis roots. The development of the hollowed root were divided into 4 stages. The 4'-hydroxyflavone contents and expression of enzymes related to 4'-hydroxyflavone biosynthesis increased synchronously with the content of MeJA during the development of hollowed root. Pathogen and programed-cell-death related genes were induced during hollowed root development. Taken together, our results provide novel insight into the importance of MeJA in the development of hollowed root and the accumulation of 4'-hydroxyflavones in Scutellaria baicalensis roots. Our results suggest that a pathogen and senescence are the two major causes for the development of hollowed root in Scutellaria baicalensis roots.